OPTIMALISASI MENANGGULANGI KEBOCORAN PADA PENYIMPANAN AIR TAWAR KM. STAR SHIP - Talizomboi Laia (UPPM, 2019)
This study aims to determine various ship systems, namely 1) the drinking water system that cannot be separated from the fresh water system, which in this system regulates the supply of fresh water for all fresh water requirements for drinking (fresh water) on the ship. 2) For a cruise that has a long route with a long time need so much clean water that it requires a large fresh water tank that its use makes the ship space inefficient.